FOREIGN DIRECT INVESTMENT IN AFRICA: - Desvaux de Marigny, Louis Jean Michel (My University, 2011)
Africa is the poorest continent and attracts the least Foreign Direct Investment (FDI). The continent is plagued by civil wars, corruption, political and macroeconomic instability, small markets, declining infrastructure, burdensome regulations, exchange rate and price instability. This project report uses Zimbabwe as a case study. Zimbabwe’s history is analysed and the prospects of renewed investment in the current climate or following a change in leadership or regime are investigated. What can be done to attract increased, beneficial FDI? What should leaders focus on in order to attract investment and foster economic growth? Which countries in Africa have succeeded in attracting FDI? What should the continent be doing as a whole to attract FDI in an increasingly competitive global arena? This study is intended as a guide for future policy makers in Zimbabwe and Africa to choose policies that will maximise FDI and thereby help to reduce poverty throughout the continent. iii
MBA - WBS
Keywords: Foreign direct investment; Zimbabwe